Crime de apropriação indébita previdenciária: uma nova classificação e suas conseqüências - Lana, Cícero Marcos Lima (2009)
The present work will deal with the correct classification of the crime of misappropriation of social security taxes and its consequences; in the truth, a new classification for this crime will be proposal, as being material. The necessity of previous exhaustion of the administrative sphere for configuration of the crime will be boarded; the work will treat, also, of the consequence that this classification as material brings for definition of the criminal type and instauration of the criminal persecution; the new decisions of the Courts will be detailed, giving themselves special relief for the alteration of the positioning of the Supreme Federal Court